Seventh International Conference on Mars Polar Science and Exploration : January 13-17, 2020, Ushuaia, Tierra del Fuego, Argentina - Smith, Isaac B.; orcid:0000-0002-4331-913X; Becerra, Patricio; orcid:0000-0002-2061-4056 (Lunar and Planetary Institute, 2020)
The conference is designed to highlight and define the current state of Mars polar research, pulling together expertise from many fields, including geology, atmospheric science, and climate science. The focus will also be on terrestrial analogs that can enhance our interpretation of remote sensing data from Mars, and on concepts for future missions. Institutional support York University, Planetary Science Institute, Centro Austral de Investigaciones Cientificas (CADIC-CONICET), University of Bern, International Association of Cryospheric Sciences, International Association of Geomorphologists, Lunar and Planetary Institute, Universities Space Research Association. Conveners Isaac Smith, York University, Planetary Science Institute, Patricio Becerra, Space Research and Planetary Sciences, University of Bern Local Organizers Andrea Coronato, Centro Austral de Investigaciones Cientificas (CADIC), Consejo Nacional de Investigaciones Cientificas y Técnicas (CONICET), Jorge Rabassa, Centro Austral de Investigaciones Cientificas (CADIC), Consejo Nacional de Investigaciones Cientificas y Técnicas (CONICET) Science Organizing Committee Isaac Smith, York University, Planetary Science Institute and 13 others Conference Organizing Committee Isaac Smith, York University, Planetary Science Institute and 7 others. PARTIAL CONTENTS: The Comparative Distribution of Flowing and Non-Flowing Icy Material in the Nereidum Montes; Mars / J. L. Collins-May, J. R. Carr, M. R. Balme, S. Brough, C. Gallagher, N. Ross, and A. J. Russell -- Detection Limits for Chiral Amino Acids Using a Polarization Camera / C. W. Cook, S. Byrne, D. Viola, C. Drouet d'Aubigny, and J. Mikucki -- Proxy Records of Frost: Frost-Driven Geomorphic Changes on Martian Sandy Slopes / S. Diniega, C. J. Hansen, and G. Portyankina -- Frequency and Morphological Consequences of Martian Gully Activity / C. M. Dundas -- Geologic Investigation of a Debris-Covered Mountain Glacier in Argyre Basin, Mars: Implications for Past Climate and History of Non-Polar Ice ...